Economics of multifunctional forestry in the Sámi people homeland region - Parkatti, Vesa-Pekka; Tahvonen, Olli (Journal of Environmental Economics and Management, 2021)
We study forestry in the Sámi people homeland to understand an ongoing conflict between conventional forestry and maintaining forests as reindeer pastures vital for indigenous Sámi livelihood. Conventional logging affects pastures by creating stand densities suboptimal to lichen growth and by decreasing old-growth forest areas, both of which are essential to reindeer survivability during the subarctic winter. Our model includes timber production, carbon sequestration, externalities on reindeer husbandry, and optimization between rotation forestry and forestry with continuous forest cover. We show that the profitability of conventional forestry relies on utilizing existing forests, an outcome we label as forest capital mining. By varying the carbon price between €0 and €60 per tCO2 and assuming a 3% interest rate, we show that continuous cover forestry, which better preserves pastures, is always optimal. A carbon price of €60 − €100 chokes off timber production. Given the present management practices and an oldgrowth forest as the initial state, the carbon choke price decreases to €14–€20. Our economic analysis on maintaining old-growth forest versus conversion to timber production is an alternative to the frequently applied approach based on carbon debts and carbon payback periods. Peer reviewed